การเปรียบเทียบการตอบสนองของภูมิคุ้มกันต่อวัคซีนไวรัสตับอักเสบบีในผู้ป่วยเอชไอวีที่ได้รับยาต้านไวรัส ในกลุ่มที่มีเม็ดเลือดขาวชนิดซีดี 4 มากกว่า 200 เซลล์ต่อลูกบาศก์มิลลิเมตรเทียบกับกลุ่มที่มีเม็ดเลือดขาวชนิดซีดี 4 มากกว่า 350 เซลล์ต่อลูกบาศก์มิลลิเมตร - พิทักษ์ เดชพรเทวัญ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
There was a high prevalence of chronic hepatitis B co-infection among HIV-infected patients. These patients also had approximately 8-fold higher in liver-related mortality than those who did not have hepatitis B co-infection. Hepatitis B infection is a preventable disease. Many treatment guidelines for HIV-infected patients recommended hepatitis B immunization in every HIV-infected person who has immunological response to anti-retroviral therapy, but did not mention which CD4 level will show the best immune response to hepatitis B vaccine. Methods From May 2012 to April 2013, in King Chulalongkorn Memorial Hospital, we conducted a prospective non-randomized study to compare immune response in HIV-infected patients with virological response to highly active antiretroviral therapy between CD4 count of more than 200 to 350 versus CD4 count more than 350 cell/cu.mm. Three doses of hepatitis B vaccine were given at 0, 1, and 6 months. Immunological response to hepatitis B vaccine was defined by anti-HBs level more than 10 IU/l at 1 month after completion of vaccination. Results Of 83 HIV-infected patients with mean CD4 count 469.7±232.5 cells/cu.mm had 73.5% overall response rate to hepatitis B vaccination. There were 33 patients (39.8%) whose anti-HBs reach more than 1,000 IU/l in this group. Of 48 patients who had CD4 count 595.4±233.5 cells/cu.mm, 38 patients (79.2%) had anti-HBs more than 10 IU/l regarded as vaccine responder. Of 35 patients who had CD4 count 297.3±45.7 cells/cu.mm, 23 patients (65.7%) were vaccine responder. There was no statistical significance among these groups (P=0.21). At the time of completion of vaccination, of 65 patients (80%) who had CD4 cell counts of more than 200 to 350 cells/ cu.mm, 52 (80%) had anti-HBs more than 10 IU. Of 18 patients who had CD4 cell counts more than 350 cells/ cu.mm, 9 (50%) were hepatitis B responders. Both groups were different with statistical significant (P=0.016). In subgroup analysis of patients who had CD4 cell counts of more than 200 to 350 cells/ cu.mm and had response to hepatitis B vaccine, 14 of 30 (60.9%) had gained CD4 cell counts to more than 350 cells/ cu.mm. And of 12 patients, 8 (66.7%) who had no response to vaccine, still had CD4 cell counts of less than 350 cells/ cu.mm. Conclusion To our knowledge, this is the first prospective study comparing immunological response to hepatitis B vaccination among HIV-infected patients between CD4 lower and higher than 350 cells/cu.mm. Even though there was no statistical significance, the better immune response seems to be in the higher CD4 group. This study supports data that suggest giving hepatitis B vaccine to patients who had CD4 more than 200 cells/ cu.mm. Among patients who had CD4 cell counts of more than 200 to 350 cells/ cu.mm, hepatitis B vaccine response rate might be better in patients whose CD4 cell counts trend to increase up to more than 350 cells/ cu.mm.